Comparison of choroidal vascularity index in rhegmatogenous retinal detachment: impact of silicone-oil vs. gas tamponade following pars plana vitrectomy - Ece Ozal; Serhat Ermis; Murat Karapapak; Omer Faruk Canli; Sadık Altan Ozal (BMC Ophthalmology)
Abstract Purpose This study aimed to evaluate the impact of silicone oil (SO) and perfluoropropane gas (C3F8) tamponade on the choroidal vascularity index (CVI) in patients undergoing pars plana vitrectomy (PPV) for rhegmatogenous retinal detachment (RRD). Methods This retrospective study included 106 patients (212 eyes) with macula-off RRD who underwent PPV with either SO (n = 60) or C3F8 gas (n = 46) tamponade. CVI and other choroidal parameters, including luminal area (LA), stromal area (SA), total choroidal area (TCA), and subfoveal choroidal thickness (SFCT), were evaluated using swept-source optical coherence tomography (SS-OCT) and compared between operated and fellow healthy eyes at postoperative months 1 and 3. In addition, direct comparisons were made between SO- and gas-treated eyes to assess the differential impact of tamponade type on choroidal metrics. Multiple linear regression analyses were conducted to investigate associations between CVI and clinical variables such as preoperative best-corrected visual acuity (BCVA), age, sex, surgical type, and tamponade type. Results No significant differences in CVI, LA, SA, or TCA were observed between operated and fellow eyes in either the SO or gas groups. Likewise, CVI values did not differ significantly between postoperative months 1 and 3 or between tamponade groups (p > 0.05). However, LA, SA, and TCA were significantly higher in SO-treated eyes than in gas-treated eyes at both follow-up visits (p < 0.05). SFCT significantly increased at month 1 in gas-treated eyes compared to fellow eyes (p < 0.001), but this difference was not significant by month 3. Conversely, SFCT was significantly lower in SO-treated eyes than in fellow eyes at both time points and continued to decrease following SO removal. The multiple linear regression analyses revealed no statistically significant associations between CVI values and preoperative BCVA, age, sex, surgical type, or tamponade type at either postoperative month 1 or month 3 (p > 0.05). Conclusion CVI values did not significantly differ between eyes treated with SO and gas tamponade, nor did they correlate significantly with postoperative visual outcomes. Although CVI provides valuable insights into choroidal health, it may not serve as a strong predictor of visual recovery in the early postoperative period. Larger, prospective studies are needed to further explore the long-term effects of different tamponade agents on choroidal vascularity and visual outcomes. Clinical trial number Not applicable.